Mixed Land Uses and Community Decline: Opportunities and Challenges for Mitigating Residential Vacancy in Peri-Urban Villages of China - Ma, Wenqiu; Jiang, Guanghui; Zhou, Tao; Zhang, Ruijuan (Frontiers in Environmental Science, 2022)
Residential vacancy is a visible symptom of community decline in peri-urban villages of China. Mixed-use development has emerged as a possible approach for land use planning to help mitigate community decline and residential vacancy. By applying an integrated framework, this paper explores whether mixed land use (MLU) can help counter residential vacancy based on the classification of four types of peri-urban villages. Results show that the degree of MLU and residential vacancy rate both present increasing tendencies. Also, impacts of MLU on residential vacancy differ across villages: the disorderly and excessive mixed uses in some villages exacerbated residential vacancy, even threatening the neighborhood safety and livability; whereas for some villages with compatible mixed uses, the land use pattern could assist in reducing the residential vacancy, as well as promoting the compact and high-density development. Undeniably, planning for the increased mixed-use environment like urban communities is unsuitable for rural communities. Sustainable planning to counter residential vacancy should combine the compatible mixed-use development together with the rational functional zoning, which is also considered as a constructive tool in mitigating community decline, and bringing human settlements development, vitality and diversity. This research contributes to reconcile residential vacancy in the depopulating and declining communities.